2014
DOI: 10.1155/2014/503825
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Anthracene in Closed System Reactor

Abstract: Polycyclic aromatic hydrocarbons (PAHs) represent a large class of persistent organic pollutants in an environment of special concern because they have carcinogenic and mutagenic activity. In this paper, we focus on and discuss the effect of different parameters, for instance, initial concentration of Anthracene, temperature, and light intensity, on the degradation rate. These parameters were adjusted at pH 6.8 in the presence of the semiconductor materials (TiO2) as photocatalysts over UV light. The main prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 27 publications
(30 reference statements)
2
23
0
1
Order By: Relevance
“…Titanium dioxide (TiO 2 ) is photocatalyst material using light to destroy environmental contaminants from wastewater due to its ability to convert them into innocuous end products such as CO 2 and H 2 O [1]. TiO 2 is one of the most prominent oxide semiconductor materials due to its high photocatalytic activity, chemical stability, nontoxicity, physical properties, and low cost [2]. However, TiO 2 has some disadvantage such as low surface area and easy recombination of the electron-hole pair [3].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) is photocatalyst material using light to destroy environmental contaminants from wastewater due to its ability to convert them into innocuous end products such as CO 2 and H 2 O [1]. TiO 2 is one of the most prominent oxide semiconductor materials due to its high photocatalytic activity, chemical stability, nontoxicity, physical properties, and low cost [2]. However, TiO 2 has some disadvantage such as low surface area and easy recombination of the electron-hole pair [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several routs were followed to remove of these dyes by multi methods as example by extraction techniques, sorption by natural and synthesized surfaces, coagulation the dyes, filtration the polluted water and by advances oxidation processes (AOPs) [9][10][11][12]. In recent years methods of AOPs were applied to remove of pollutants from waste water [13,14]. Treatment of pollutants by AOPs most likely combined with using heterogeneous semiconductor in presence of photo.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the formation of nitro-anthracene from the degradation of anthracene by the OH • and NO3 • has been investigated using quantum chemical calculations [22,23]. Karan et al reported the photocatalytic degradation of anthracene under UV irradiation on TiO2 nanoparticles, they found that the main product of oxidation of Anthracene is 9,10-Anthraquinone, which is safer for the environment than Anthracene [24]. Kozak et al removed PAHs from the pretreated coking wastewater by using CaO2, Fenton reagent under UV irradiation [25].…”
Section: Introductionmentioning
confidence: 99%